I WATCH MOVIES: A LOOK INTO HOW INFORMAL L2 LEARNERS ACQUIRE A NEW LANGUAGE - Sya'baningrum Prihhartini; Fahmy Hasan (Universitas Islam Negeri Sunan Gunung Djati, 2020)
The present study sought to investigate how much independent second language learners acquire new language through movies. With the growing of Over-The Top (OTT) media services such as Netflix and Viu, which provide movies in many languages and from various nations, the possibility for public in general to watch any movies in any language is limitless, hence exposing them to acquire a new language. Two surveys, one about English and another about Korean acquisition, were conducted via Google Form and distributed via social media to examine how much informal L2 learners retrieve their stored input acquired from the movie viewing. Data collected were analyzed using mixed method data analysis. The result show that Korea movie viewers could recall more words than the English movie viewers. Korean movie viewers also seem to perform more on productive retrieval as they use the words they get from movies to communicate with their community. English movie viewers, on the other hand, seem to perform more on receptive retrieval as they can understand the story of the movies without needing subtitle. The findings suggest that watching movies greatly expose viewers to language input, which can be a great source of output when interacting within the movie-based community that they belong to.